School Digital Transformation: Design and Construction of New Student Admissions Website - Suci Indah Sari; Mahendra Adhi Nugroho (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Suwargi Buwana Djati Integrated MA is one of several schools located in Cirebon area. The purpose of this research is to develop a website for the New Learner Information System at Suwargi Buwana Djati Integrated MA. CodeIgniter framework, Visual Studio Code editor, and PhpMyAdmin database management systems are used as tools for the development of information systems . One of the system development methods used is the Waterfall model, which includes analysis , design , implementation , and testing. The results of this research is a website called the New Student Admission Management Information System at Suwargi Buwana Djati Integrated MA which can operate properly .